Homocysteine, MTHFR and risk of venous thrombosis: a meta-analysis of published epidemiological studies. - Den Heijer, M; Lewington, S; Clarke, R (2005)
CONTEXT: It has been suggested that elevated total plasma homocysteine levels are associated with the risk of venous thrombosis. OBJECTIVE: To assess the relationship of homocysteine and the MTHFR 677TT genotype and the risk of venous thrombosis by conducting a meta-analysis of all relevant studies. DATA SOURCES AND SELECTION: Studies (case-control or nested case-control) were identified by searches of electronic literature for relevant reports published before July 2003 on homocysteine and the MTHFR 677TT genotype and venous thrombosis as an end-point, by hand-searching reference lists of original articles (including meta-analyses) on this topic and by contact with investigators in the field. DATA EXTRACTION: A meta-analysis of 24 retrospective (n = 3289 cases) and three prospective studies (n = 476 cases) was carried out to examine the association of homocysteine with venous thrombosis. A meta-analysis of 53 studies (n = 8364 cases) of the MTHFR 677TT genotype (that increases homocysteine) was carried out to assess if this association is causal. DATA SYNTHESIS: A 5 micromol L(-1) higher measured homocysteine level was associated with a 27% (95% CI: 1-59) higher risk of venous thrombosis in prospective studies and a 60% (95% CI: 10-134) higher risk in retrospective studies. The 677TT genotype was associated with a 20% (95% CI: 8-32) higher risk of venous thrombosis compared with the 677CC genotype. In contrast with non-American studies, the 677TT genotype had no effect on venous thrombosis in North America, due probably to the higher intake of folate and riboflavin in North America. CONCLUSION: This meta-analysis of prospective and retrospective studies demonstrates a modest association of homocysteine with venous thrombosis. The elevated risk associated with the MTHFR 677TT genotype provides some support for causality.